Permasalahan Konsep Harga Dan Solusi Ekonomi Islam Terhadap Mekanisme Pasar Modern - Nunung Robiatul Rifkah; Besse Khusnul Khatimah (CV. ULIL ALBAB CORP, 2023)
Price that occur in the market can undergo changes and can naturally return to normal. The ideal market mechanism is one in which price power is determined by supply and demand. However, in the current area, there is a need for supervision from the government so that market distortion does not occur. Many frauds are committed by sellers so that they get a bigger profit. This study uses a qualitative method where the author actively conducts research from various sources. As for the study of the findings found to overcome the existing problems, namely examining the teachings of the Islamic concept which prohibits all practices that can harm one party. Islam has provided concepts according to shari’a values such as the application of the principles of justice, honesty, openness and mutual consent and voluntarily in setting prices and market mechanisms. The muslim scholar Ibn Taimiyah also contributed to the idea of Islamic economics that the market needs to be subject to price intervention in certain circumstances in order to create justice in society.